Mies contra Le Corbusier - Hartoonian, Gevork, author. Link
1 online resource
Keywords: "In Mies Contra Le Corbusier, Gevork Hartoonian embarks on a captivating exploration of the architectural ideologies embodied in the works of Mies van der Rohe and Le Corbusier. Focusing on the non-synchronicity inherent in their approaches to the tectonics of the column and wall, Hartoonian conducts a comparative analysis of carefully selected diachronic projects from each architect. This insightful journey unravels the architects' ideological stances within the ongoing dialogue between modernity and tradition. Hartoonian sheds light on the inclination of Mies and Le Corbusier towards a frameless architecture, a characteristic prominently displayed in their late works. Drawing inspiration from Marxian philosophy, the author contends that significant technological developments play a crucial role in shaping subjectivities across the cultural spectrum, creating an uneven dissemination. The frame, in Hartoonian's lens, transcends the boundaries of a single building, becoming a lens through which to frame a nuanced understanding of the urban landscape and tectonics. Mies Contra Le Corbusier stands as a thought-provoking exploration that not only unveils the intricacies of architectural history but also offers profound insights into the cultural and technological forces shaping the built environment. This book will be of interest to researchers and students of architectural history and theory. Additionally, it offers a timely discussion of Mies and Le Corbusier's contributions to architecture's contemporaneity for the younger generation of architects"--